Improved assessment of cartilage repair tissue using fluid-suppressed (23)Na inversion recovery MRI at 7 Tesla: preliminary results - Chang, Gregory (2012)
OBJECTIVES: To evaluate cartilage repair and native tissue using a three-dimensional (3D), radial, ultra-short echo time (UTE) (23)Na MR sequence without and with an inversion recovery (IR) preparation pulse for fluid suppression at 7 Tesla (T). METHODS: This study had institutional review board approval. We recruited 11 consecutive patients (41.5±11.8 years) from an orthopaedic surgery practice who had undergone a knee cartilage restoration procedure. The subjects were examined postoperatively (median=26 weeks) with 7-T MRI using: proton-T2 (TR/TE=3,000 ms/60 ms); sodium UTE (TR/TE=100 ms/0.4 ms); fluid-suppressed, sodium UTE adiabatic IR. Cartilage sodium concentrations in repair tissue ([Na(+)](R)), adjacent native cartilage ([Na(+)](N)), and native cartilage within the opposite, non-surgical compartment ([Na(+)](N2)) were calculated using external NaCl phantoms. RESULTS: For conventional sodium imaging, mean [Na(+)](R), [Na(+)](N), [Na(+)](N2) were 177.8±54.1 mM, 170.1±40.7 mM, 172.2±30 mM respectively. Differences in [Na(+)](R) versus [Na(+)](N) (P=0.59) and [Na(+)](N) versus [Na(+)](N2) (P=0.89) were not significant. For sodium IR imaging, mean [Na(+)](R), [Na(+)](N), [Na(+)](N2) were 108.9±29.8 mM, 204.6±34.7 mM, 249.9± 44.6 mM respectively. Decreases in [Na(+)](R) versus [Na(+)](N) (P=0.0.0000035) and [Na(+)](N) versus [Na(+)](N2) (P=0.015) were significant. CONCLUSIONS: Sodium IR imaging at 7 T can suppress the signal from free sodium within synovial fluid. This may allow improved assessment of [Na(+)] within cartilage repair and native tissue.